2021
DOI: 10.1002/stem.3388
|View full text |Cite
|
Sign up to set email alerts
|

Enteric mesenchymal cells support the growth of postnatal enteric neural stem cells

Abstract: Interplay between embryonic enteric neural stem cells (ENSCs) and enteric mesenchymal cells (EMCs) in the embryonic gut is essential for normal development of the enteric nervous system. Disruption of these interactions underlies the pathogenesis of intestinal aganglionosis in Hirschsprung disease (HSCR). ENSC therapy has been proposed as a possible treatment for HSCR, but whether the survival and development of postnatal-derived ENSCs similarly rely on signals from the mesenchymal environment is unknown and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 61 publications
0
21
0
Order By: Relevance
“…Live cell imaging was performed as previously described. 28 Changes of GFP intensity, indicative of calcium activity, in up to 35-selected cells in 3 separate preparations were evaluated in response to varying doses of acetylcholine (ACh, Fig. 4E ʹ), demonstrating activation in a significant proportion of cells as compared to control ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Live cell imaging was performed as previously described. 28 Changes of GFP intensity, indicative of calcium activity, in up to 35-selected cells in 3 separate preparations were evaluated in response to varying doses of acetylcholine (ACh, Fig. 4E ʹ), demonstrating activation in a significant proportion of cells as compared to control ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Enteric neurons in the hindgut are derived from separate vagal and sacral neural crest cells [ 23 , 24 ]. Neural spheres extracted from colons of E13.5d mice mainly contain neural crest cells (NCCs) ( Figure S2A–E ) and enteric mesenchymal cells (EMCs) [ 25 , 26 ], while reciprocal induction of EMCs and NCCs promotes the development of the gut [ 27 ]. One study also showed that neural spheres could improve their function after being transplanted into an aganglionic embryonic distal colon [ 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…Wholemount staining of LMMP tissues was performed as previously reported [ 62 , 63 ]. Tissues were incubated with blocking buffer containing 10% donkey serum, 10% bovine serum albumin, and 1% Triton X-100 for 1 h at room temperature.…”
Section: Methodsmentioning
confidence: 99%